التكييف الفقهي لجريمة الابتزاز عبر الوسائل الالكتروني وعقوباتها في الشريعة الإسلامية: Fiqh Adaptation (al-Takyif al-Fiqhi) of the Crime of Extortion through Electronic Means and Its Penalties in Islamic Law - Sabil Alanazi, Sultan; Ali, Abdul Karim; Abdul Khalil, Shahidra (Jurnal Fiqh, 2023)
The development in the technical field was accompanied by the emergence of new forms of crimes, including the crime of extortion, which moved from the traditional reality to the virtual world, and the technical means of communication became a lush ground for it. The forms and methods of committing it also varied, and accordingly this research seeks to define this crime and explain its characteristics and international legislation to reduce it. The study also seeks to clarify the jurisprudential adaptation of this emerging incident and tries to liberate the jurisprudential principle on which it is built. The researcher used the analytical descriptive approach due to its suitability for the variables of the study. The research concludes several results, the most prominent of which are: (i) the importance and necessity of al-takyif al-fiqhi to demonstrate the comprehensiveness of Islam for all facts and calamities, (ii) the crime of electronic extortion changes its form and accelerates with digital growth, the importance of holding developmental courses in the technical aspects of workers in the judicial sector, and (iii) to understand the characteristics of this milieu, so that the judge and the mufti are fully aware of the cases or fatwas referred to them that enable them to clarify the estimated punishment and prevent these crimes.